Structuring information in the system of training masters of natural sciences - Hladun, T. (Journal of Education, Health and Sport, 2021)
The article analyzes the philosophical, psychological, pedagogical, educational, and methodological literature on the research problem; the essence of the concepts “structuring of educational information”, “professional and pedagogical training of masters of natural sciences for structuring educational information” is revealed, methods of structuring educational information are analyzed, forms of presenting educational information are revealed.